PENGARUH E-SERVICE QUALITY TERHADAP E-SATISFACTION DAN E- LOYALTY NASABAH PENGGUNA MANDIRI ONLINE - Budiman, Arief; Yulianto, Edy; Saifi, Muhammad (Profit: Jurnal Adminsitrasi Bisnis, 2020)
This research aims to investigated the effect of e-service quality as independent variabel on e-customer satisfaction and e-customer loyalty as dependent variabel. This research is a quantitative approach with type of explanatory research. The data used are primary data obtained by distributing questionnaires directly to user mandiri online in six cities, namely Jember, Situbondo, Probolinggo, Bondowoso, Lumajang, Banyuwangi,. Purposive sampling are used as sampling method in this study.115 respondent are collected. Data analysis use Structural Equation Model (SEM ). The conclusion show that online service quality have positive effect and significant on e-satisfaction and e-loyalty mandiri online userâ€™s.Â